ANALISIS BIONOMI IKAN KARANG DI PERAIRAN KABUPATEN RAJA AMPAT, PROVINSI PAPUA BARAT - Akhmad Fauzi; Daniel R. Moninjta (Buletin PSP, 2009)
The fishery resources of Raja Ampat Regency in West Papua Province have shown a declining trend in terms of total production. In order to sustainably manage the fishery for future utilization, a baseline analysis needs to be carried out as a tool for sustainable management. This paper attempts to indicate baseline performance of fisheries from bioeconomic perspectives. One of important results of bioeconomic analysis is that currently there is no indication of overfishingyet in Raja Ampat areas. Total production in open access level has showen 3.97ton per week. Effort in sole owner level (MEY) has showen 9,06 trip per week. Economic rent undersole owner regimeis around Rp.43.040.425,19 per week. This condition has shown that catch per unit effort has been efficient, so that fish harvest has been better and will be followed by maximum economic rent.Keywords: bionomic analysis, fisheries resources, open access, Raja Ampat-West Papua, sole owner